2000
DOI: 10.1007/s002139900316
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effect of 7-nitroindazole in the forced swimming test in rats

Abstract: Our findings suggest that NO might be an important modulator of depression in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 13 publications
7
72
0
5
Order By: Relevance
“…This notion is further supported by recent studies which have demonstrated that NOS inhibitors are as efficacious as antidepressants in reducing the duration of immobility in the mouse forced swimming test -a preclinical antidepressant screening procedure [4][5][6]. These anti-immobility effects are blocked by prior administration of the NO precursor, L-arginine [4,5].…”
Section: Introductionsupporting
confidence: 59%
“…This notion is further supported by recent studies which have demonstrated that NOS inhibitors are as efficacious as antidepressants in reducing the duration of immobility in the mouse forced swimming test -a preclinical antidepressant screening procedure [4][5][6]. These anti-immobility effects are blocked by prior administration of the NO precursor, L-arginine [4,5].…”
Section: Introductionsupporting
confidence: 59%
“…Accordingly, a rapidly increasing body of evidence coming from pharmacological studies in animals argues in favour of this hypothesis. [26][27][28][29][30][31][32][33][34][35] Finally, a landmark study by Akbarian et al, 36,37 followed by further histopathological investigations, 38 argues that nitrinergic neurons are pathologically altered in SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…Drug doses were selected according to behavioral and neurochemical studies showing the drugs to have the intended effect [23,25] . 7-NI and L -arginine, at the doses used in this study, were previously shown to have no effect on locomotor activity [3,4,16] . Since it was reported that maximal inhibition of NOS by 7-NI occurs at 30 min after intraperitoneal injection [24,25] , 7-NI (2.5, 5, 10 mg/kg), L -arginine (200 mg/kg) or vehicle was administered intraperitoneally 30 min prior to the three-panel runway task, which was performed when the animals fulfilled the learning criteria.…”
Section: Drugs and Treatmentsmentioning
confidence: 99%
“…NO was implicated in the regulation of various behavioral, cognitive and emotional processes such as aggression, anxiety, depression and locomotion [2][3][4] . It has recently been suggested to play a role in modulating learning and memory [5] .…”
Section: Introductionmentioning
confidence: 99%